Enablers and Barriers to Hand Hygiene among Health Workers at Mbarara Regional Referral Hospital - Niyonzima , Vallence; Luwaga, Rachel; Beinempaka , Florence (Journal of Health, Medicine and Nursing, 2023)
Purpose: Hospital acquired infections (HAIs) are a public health problem that is more prevalent in developing countries than in developed countries. Hand hygiene is a prime preventive measure for HAIs. This study assessed barriers and enablers to hand hygiene among health care workers (HCWs) in a developing country at Mbarara Regional Referral Hospital. Methodology: A descriptive cross-sectional design was employed. HCWs providing care to patients admitted on the selected wards were recruited. Data were collected by trained RAs from participants who fulfilled the eligibility criteria using a semi-structured questionnaire. Findings: The majority (73.4%) of the participants reported lack of hand hygiene protocols on the ward. The barriers and enablers were elicited using a Likert scale. The enablers to hand hygiene were water being visibly clean (M = 3.5, SD = 0.7) and availability of running water on the ward (M = 3.4, SD = 0.8). Barriers to hand hygiene identified were: lack of audits on hand hygiene compliance on the wards (M = 1.7, SD = 0.9), posters illustrating hand hygiene techniques are not displayed on the wards (M = 2.1, SD = 1.0) and alcohol hand rubs are not routinely distributed (M = 2.1, SD = 0.9). Unique Contribution to Theory, Practice and Policy: Donabedian model is a validated model used in quality improvement in health care. There is need to include training for health care workers in hand hygiene, ensure availability of hand hygiene protocols, and include mechanisms for monitoring to improve hand hygiene.